Statistical Analysis of the Spatial and Functional Localization of Education Subsystems in Russian Regions - Dmitry A. Endovitsky; Yury I. Treshchevsky; Evgeny A. Rudnev (Moscow Polytechnic University, 2019)
The paper considers the specifics of the spatial and functional localization of regional education subsystems in the Russian Federation. Such subsystems include pre-school education, school education, secondary vocational education, and higher education. A set of indicators is suggested that can be used to assess the development stage of these subsystems. Cluster analysis made it possible to group the country's regions according to the parameters of the education system, and determine the major characteristics of these groups (virtual clusters). Development tendencies of the education subsystems in the regions of each virtual cluster from 2010 to 2016 were analysed to identify the strong and the weak points of each group.